Medium of instruction in physical education students. - Vaskov Urij Vadimovich (Kharkov National Pedagogical University, 2011)
In the article are examined the theoretical questions of determination of facilities of studies as important component organization of process of physical education in general educational establishments. Going of different authors light up near determination of concept "facilities of studies", their functions and classification. The questions of determination of sources of facilities of studies and their composition are separately probed. As one of variants, classification of facilities of studies, which are used in the process of physical education of students and also their influence on planning of maintenance of athletic education and technology of organization of educational process, is offered.